Robot Peraga 12 Gerakan Pengaturan Lalu Lintas Berbasis Arduino Mega 2560 - bara, tri wahyono; Rosyid, Rahman; Prasetyo, Muhamad Awiet Wiedanto (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2021)
Bhayangkara is a work unit for Education to channel interest, develop talent, increase knowledge, abilities, skills and experience of Scouts in various fields. One of the activities of the Saka Bhayangkara member is Traffic Krida which aims to assist the police in traffic including regulating traffic flow. Traffic Management in certain circumstances and the use of roads other than for traffic activities using hand movements, sound signals, light signals and other aids in certain circumstances. The purpose of this study is to design a robot as a learning media for Arduino Mega based traffic control movement with a remote controller which is expected to be a learning medium and is useful as an interesting visual aid and can add interest for members of Saka Bhayangkara to learn regulatory movements traffic. The development method used in this study is the waterfall method. The results of this research are a system in the form of a robot learning movement learning Arduino mega-based traffic control with a remote controller that has gone through the unit testing stage and shows all the features running well. Keywords: Arduino, Traffic, Saka Bhayangkara